inggris - Nur Asrawati; Sitti Fatimah Sangkala Sirate (MaPan : Jurnal Matematika dan Pembelajaran, 2022)
This study aims to determine the increase in students' mathematical creativity through the auditory, intellectual, repetition (AIR) learning model in class XI students of SMK Techno Terapan Makassar. Creativity referred to in this study pays attention to 3 aspects of indicators, namely fluency, flexibility, and novelty. This research is research class action (PTK). The subjects of this study were students of class XI at SMK Techno Terapan Makassar. The results showed that there was an increase in creativity in learning mathematics through the auditory, intellectual, repetition (AIR) learning model. Student test results seen based on the percentage per indicator increased from cycle I to cycle II seen in the aspect of fluency 66.66% increasing to 81.48%, the aspect of flexibility 62.96% increasing to 77.78%, and the novelty aspect increasing 33.33% to 48.14%. the learning completeness criteria in cycle I was 55.55% and classically complete in cycle II was 77.77% or as many as 22 people who scored . Data from the analysis of teacher activity in cycle 1 increased by 60.42% to 72.90% while the results of student activity analysis in cycle 1 amounted to 56.26% increased to 70.92%. From the research results obtained, it can be concluded that the Auditory, Intellectual, Repetition (AIR) learning model can increase the mathematical creativity of class XI students of SMK Techno Terapan Makassar.